The dimensional structure of the Yale-Brown Obsessive-Compulsive Scale for Pathological Gambling: functional differences between true compulsions and compulsive behavior. Issue 1 (2nd January 2021) - Moritz, Steffen; Bücker, Lara; Wittekind, Charlotte; Gawęda, Łukasz; Gehlenborg, Josefine
ABSTRACT: The present study examined the factorial structure of the Pathological Gambling Adaptation of the Yale-Brown Obsessive-Compulsive Scale (PG-YBOCS) to delineate similarities and differences between thoughts and behavior related to pathological gambling (PG) versus obsessive-compulsive disorder (OCD). The PG-YBOCS was administered in its self-report version in 265 individuals with gambling problems. A factor analysis revealed a two-dimensional structure. The first dimension represented gambling severity; the second dimension reflected resistance to thoughts/urges and behavior. The first but not the second dimension was strongly correlated with depression and the severity and functional relevance of gambling problems. When the standard factor structure (thoughts vs. behavior) was adopted, depression, which is correlated with obsessions but not compulsions in OCD, was correlated with both subscales. Length of illness, a correlate of compulsions in OCD, showed no association with gambling. The present study corroborates factor analyses on the Y-BOCS, demonstrating the existence of an independent resistance dimension. Unlike in OCD, no evidence for independent factors tapping thoughts versus behaviors was obtained, which likely reflects the addictive rather than compulsive nature of problem gambling. Specific correlates of thoughts and behavior in OCD were not confirmed in gambling, further speaking for functional differences between the two disorders.